Economical biomass cat litter using eggshell / Muhammad Nabil Ahmad Sukri - Ahmad Sukri, Muhammad Nabil (2019)
Most commercially produced clay cat litters such as bentonite clay cat litter nowadays have raised issues to pet owners since they are toxic, non-biodegradable and have no natural odor controlling features. Thus, a study to develop litter from biomass was carried out to produce a cat litter from biomass that is biodegradable, scoopable, odor control and economical properties in order to overcome those problems. In this study, biomass materials; eggshell were processed into cat litter formulations and the results were compared. Firstly, the eggshell were cleaned properly and dried to remove moisture content and grinded to reduce their particle size. Then, the grinded eggshells were then mixed with xanthan gum as clumping agent, sodium bicarbonate as deodorizer, and glycerol as dust retardant to form mixtures of cat litter. For the purpose of enhancing the adsorptivity of the cat litter and flushability, hydrogel is added into cat litter formulations. Two types of hydrogel were used into this eggshell cat litter where a superabsorbent (carboxymethylcellulose/starch hydrogel) and a consecutive hydrogel biochar product were added into 2 different samples of eggshell cat litter. The samples were tested to compare with all of those raw materials in terms of their clumping activity, absorption capacity and dust formation.